The Correlational Relationship of the Cognitive Style (Abstract–Concrete) with the Perceptual Ability in Processing Visual Illusion among Students of Institutes of Fine Arts - عباس, عماد هاشـم مجيد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
cognitive style (abstract-concrete) is one of the many cognitive styles that gives people unique characteristics and traits and distinguishes between abstract and concrete people in how they process visual stimuli. If individual differences in dealing with topics and information about the outside world appear in their cognitive abilities to analyze external influences, then the effectiveness of the cognitive process is linked to the way they perceive sensory information, process it, and integrate it with what is in the memory store Unifying and transforming it from an abstract sensory image (transforming it from its objective image) into a conceptual image resulting from the act of knowledge and what is related to it, i.e. transformed into new cognitive structures that differ in their characteristics from the pattern that formed them. The research problem lies in how to transform the abstract image (images of optical illusion) into concrete images depending on the cognitive style (abstraction - concreteness). This is done by answering it through the research objectives and identifying the correlation of the cognitive style (abstraction - concreteness) with the cognitive ability in processing the visual illusion, as well as identifying the differences in the visual illusion according to the following variables: - Cognitive style) Abstraction - Concreteness (b - Gender) Males - Females (c - Departments of Fine Arts Institutes. The current research aimed to identify the correlation of the cognitive style (abstraction - concreteness) with the cognitive ability in processing the visual illusion, as well as identifying the differences in the visual illusion according to the following variables: 1- Cognitive style (abstraction - concreteness). b - Gender) Males – Females Departments of Fine Arts Institutes The research was limited to studying the visual sensory aspect, and the research sample was determined: the Fine Arts Institute for the departments (plastic arts, design, architecture, Arabic calligraphy and decoration). The research was based in its theoretical framework on the sequence of absolute information, which it dealt with in order: now the cognitive methods and how they are and their development, the definition of cognitive methods, their distinguishing characteristics... and psychological differentiation, as well as classifying them according to the chronological sequence, arriving at the cognitive method (abstraction - visual) and the physiological foundations of the optical illusion - (the function of the eye, the physiology of the eye, and the state of how the optical illusion occurs for any part of the eye, optical illusions or visual art), and perception and its stages that it passes through from visual sensory perception to mental perception (cognitive) and I reviewed the relationship between the cognitive method (abstraction - love) and the optical illusion, arriving at indicators of framework… The research came out with a number of results, the most important of which are There is a positive correlation and statistical significance of (0.87) between the cognitive style (abstraction - causality) and the cognitive ability in processing the visual illusion, i.e. the greater the student’s ability to abstract, the greater the ability to process the visual illusion, and the greater the causality, the less the ability to process the illusion Visual. The research reached conclusions related to the importance of the sensory cognitive process and This is about the optical illusion and the extent to which it is affected by the abstract-concrete cognitive style (and what it shows of distinguishing abstract people with their high cognitive ability in discovering the formal relationships of the optical illusion, and they are): and the high psychological differentiation From their abstract peers, and they are (those with low psychological differentiation), and among the recommendations: the importance of using selection in departments that teach art and art education in order to increase and develop the abstract style among students and crystallize their creative abilities. The proposals included: conducting studies that discuss the aesthetic impact of shapes Illusion according to other formal and artistic vocabulary).